Using the electronic health record for assessment of health insurance in community health centers. (23rd January 2016) - Hatch, Brigit; Tillotson, Carrie; Angier, Heather; Marino, Miguel; Hoopes, Megan; Huguet, Nathalie; DeVoe, Jennifer
Abstract : Objective To demonstrate use of the electronic health record (EHR) for health insurance surveillance and identify factors associated with lack of coverage. Materials and Methods Using EHR data, we conducted a retrospective, longitudinal cohort study of adult patients ( n  = 279 654) within a national network of community health centers during a 2-year period (2012–2013). Results Factors associated with higher odds of being uninsured (vs Medicaid-insured) included: male gender, age >25 years, Hispanic ethnicity, income above the federal poverty level, and rural residence ( P  < .01 for all). Among patients with no insurance at their initial visit ( n  = 114 000), 50% remained uninsured for every subsequent visit. Discussion During the 2 years prior to 2014, many patients utilizing community health centers were unable to maintain stable health insurance coverage. Conclusion As patients gain access to health insurance under the Affordable Care Act, the EHR provides a novel approach to help track coverage and support vulnerable patients in gaining and maintaining coverage.